An Interactive Allyship and Privilege Workshop for Trainees in Medicine - Janette Tang; Rebecca Chen; LaMisha Hill Weller; Christy Boscardin; Odinakachukwu Ehie (Association of American Medical Colleges, 2024)
Introduction Despite growing efforts to increase diversity in recruitment and to teach principles of diversity, equity, and inclusion (DEI), representation of individuals underrepresented in medicine continues to fall short. This demonstrates a need for efforts that target the work environment and culture to increase retention alongside existing recruitment initiatives. We designed this interactive allyship workshop with a focus on building skills necessary for being an ally that has been missing in existing allyship curricula. Methods This workshop was led by multidepartmental faculty with experience in DEI training. Participants engaged in a number of interactive activities to reflect on their own identities and privilege and practiced ways to engage in difficult conversations. Prior to the workshop, participants completed a survey that was repeated at the workshop's completion to evaluate their perspective change and understanding of allyship. We also collected responses to a self-reflective exercise during the workshop. Results Participants included 68 anesthesia and surgery attendees, 53 of whom (78%) completed the postsurvey. Participants strongly agreed that this workshop was important to the workplace and medical training. Themes from the self-reflective exercises included endorsement of sponsorship and mentorship activities, community support, and advocacy. Discussion Interactive skill-building activities are important and effective at helping trainees develop as allies. Long-term follow-up is needed to assess longitudinal knowledge retention and translation into behavioral change to create a more inclusive and supportive work environment.